Understanding environmental justice capital in China — a new framework to study environmental justice in contexts - Shao, Mengqi; Tan-Mullins, May; Chan, Faith Ka Shun (Springer, 2020)
Environmental justice has drew worldwide attention since the 1982 protest in USA to against duping toxic waste. In the globalization era, worldwide scholars and environmental activists are actively engaged in related studies and social movements. However, these researches and movements usually ignore the influences of local contexts on local environmental justice configurations, including related researches in China. Whilst, evidences have been provided that different forms of capital from contexts, such as economic, social, political, natural capital and cultural capital, will affect the local concept of environmental justice. That is to say environmental justice should have different discourse from what has been researched in western countries in different contexts. Thus, this research will discuss the common ground of environmental justice study framework and promote the new conceptual framework “environmental justice capital” for having a better understanding environmental justice in contexts. Additionally, the framework of “environmental justice capital” will be put in Chinese contexts as a preliminary discussion to get an initial image of environmental justice in China.